The pathless sky: violence and culture in First World War air services - Doyle, J (2019)
The First World War has almost always been the impetus behind new developments in critical studies of violence, in fields as diverse as psychology, strategic studies, and cultural history. Western Front infantry soldiers remain central to cross-disciplinary interpretations of combatant experience, identity, and community. This thesis reframes these fundamental relationships between war violence and community by considering an under-explored First World War battlefield: the air. It explores French, British, and American fighter pilots as a transnational combat culture emerging in dialogue with a distinctive, new type of warfare.